Western USA - Balfour, Amy C.; Bao, Sandra; Benson, Sara; Ward, Greg (Carlton, Victoria, Australia Lonely Planet, 2016)
The world's leading travel guide publisher Lonely Planet Western USA is your passport to the most relevant, up-to-date advice on what to see and skip, and what hidden discoveries await you. Watch Old Faithful at Yellowstone National Park, wander through the diverse neighborhoods of San Francisco, or marvel at the Grand Canyon; all with your trusted travel companion. Get to the heart of Western USA and begin your journey now! Inside Lonely Planet's Western USA Travel Guide: *Color maps and images throughout *Highlights and itineraries help you tailor your trip to your personal needs and interests *Insider tips to save time and money and get around like a local, avoiding crowds and trouble spots *Essential info at your fingertips - hours of operation, phone numbers, websites, transit tips, prices *Honest reviews for all budgets - eating, sleeping, sight-seeing, going out, shopping, hidden gems that most guidebooks miss *Cultural insights give you a richer, more rewarding travel experience - history, Native American culture, Western cuisine, arts & architecture, land & wildlife *Over 35 color maps *Covers California, Los Angeles, San Francisco, Pacific Northwest, Rocky Mountains, Southwest, Las Vegas and more The Perfect Choice: Lonely Planet Western USA, our most comprehensive guide to Western USA, is perfect for both exploring top sights and taking roads less traveled * Looking for a guide focused on Los Angeles and San Francisco? Check out Lonely Planet's Los Angeles and San Francisco guides for a comprehensive look at all these cities have to offer; or Pocket Los Angeles and Pocket San Francisco, handy-sized guides focused on the can't-miss sights for a quick trip.
Plan your trip -- On the road: California -- Pacific Northwest: Washington ; Oregon -- Rocky Mountains: Colorado ; Wyoming ; Montana ; Idaho -- Southwest: Nevada; Arizona ; Utah ; New Mexico -- Understand Western USA --Survival guide.
At head of title: Lonely Planet
Includes bibliographical references and index.
Keywords: West (U.S.) -- Guidebooks; West (U.S.) -- Description and travel